The assortment of ceramic building materials from the pottery workshop of Sextus Me(u)tillius Maximus at Crikvenica (Croatia) : Asortiman građevinske keramike iz keramičarske radionice Sexta Me(u)tillia Maxima u Crikvenici (Hrvatska) - Konestra, Ana (Array, 2020)
Roman building materials, especially brick and tiles (tegulae and imbex) marked a new era in the architecture of Roman Dalmatia. While imported materials seem to still form the bulk of the evidence, recently identified and definitely located local productions provide the possibility to place these products within a technological and economical framework. The in-depth analysis of the array of ceramic building materials (CBM) of the workshop of Sextus Me(u)tillius Maximus in Crikvenica (north-eastern Adriatic) evidences their forming methods and production technology, while some distribution aspects and their role within the rural economy indicate their relevance within the regional CBM market. This paper will highlight such aspects and place them within a wider debate on the onset of production, the organisation of rural property, and the transmission of technology and knowledge through the adoption of “Roman style” architectural solutions.